Rulemaking in super-RTAs: Implications for China and India - Suparna Karmakar (Bruegel, 2014)
The faltering Doha round has led to a renewed focus on large regional trade agreements. There are two super-RTAs in the making in the Asia-Pacific and one in the Atlantic, all with rather ambitious negotiation targets, and presented as alternate means to reset global trade rules and take the multilateral trade liberalisation agenda forward. So what does this development mean for large emerging markets such as China and India that are on the fringes of these regional trade negotiations? Can these agreements become alternate means of pressuring these Asian economies to follow new trade rules set by industrialised countries, especially given the progressive erosion of the policy dominance of industrialised countries and the strong dissenting voice of developing countries in the Doha Round? This paper examines how super-RTAs may emerge as game changers in the multilateral trading system as promulgated by the WTO, and the implications for China and India. The paper analyses the new economic governance system that is likely to emerge given the renewed interest in regionalism, and argues that while the super-RTAs will not be entirely benign in their impact on China and India, rather than forcing these economies to accept the higher new regulatory standards enshrined in the super-RTAs, a distinct possibility in the medium-term is the emergence and entrenchment of a dual regulatory regime in these economies.
Keywords: 330